The Social Context of Criminal Threat, Victim Race, and Punitive Black and Latino Sentiment. (12th March 2018) - Stewart, Eric A; Johnson, Brian D; Warren, Patricia Y; Rosario, Jordyn L; Hughes, Cresean
Abstract: A well-established body of research focuses on the relationship between criminal threat and the exercise of formal social control, and a largely separate literature examines the effects of victim race in criminal punishment. Despite their close association, few attempts have been made to integrate these related lines of empirical inquiry in the sociology of punishment. In this article, we address this issue by examining relationships among criminal threat, victim race, and punitive sentiment toward black and Latino defendants. We analyze nationally representative survey data that include both subjective and objective measures of criminal threat, and we incorporate unique information on victim/offender dyads to test research questions about the that role victim race plays in the formation of anti-black and anti-Latino sentiment in the criminal justice system. The results indicate that both subjective perceptions of criminal threat and minority population growth are significantly related to punitiveness among whites, and that punitive sentiment is enhanced in situations that involve minority offenders and white victims. Moreover, we show that aggregate indicators of racial threat strongly condition the effect of victim race on punitive attitudes. Implications of these findings are discussed in relation to racial group threat theories and current perspectives on the exercise of state-sponsored social control.